Antecedents and the mediating effect of customer-restaurant brand identification. Issue 2 (17th February 2020) - Han, Sung Ho; Ekinci, Yuksel; Chen, Cheng-Hao Steve; Park, Mi Kyeong
ABSTRACT: This study develops a framework of customer-restaurant brand identification and tests a full and partial mediation model of brand identification to understand the way in which customers develop brand identification in the restaurant sector. The models are tested via customer data using a structural equation modeling (SEM) approach. The findings suggest that brand identification by customers is influenced by four antecedents: brand prestige, symbol attractiveness, self-congruence, and brand experience . The study confirms that brand identification fully mediates the effect of self-congruence on brand loyalty. The effects of brand prestige, symbol attractiveness, and brand experience on brand loyalty are partially mediated by brand identification. This study contributes to the branding strategies of global restaurants to secure a competitive edge.